An experimental evaluation of electrical skin conductivity changes in postmortem interval and its assessment for time of death estimation - Canturk, Ismail; Karabiber, Fethullah; Celik, Safa; Sahin, M. Feyzi; Yagmur, Fatih; Kara, Sadik (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
In forensic medicine, estimation of the time of death (ToD) is one of the most important and challenging medico-legal problems. Despite the partial accomplishments in ToD estimations to date, the error margin of ToD estimation is still too large. In this study, electrical conductivity changes were experimentally investigated in the postmortem interval in human cases. Electrical conductivity measurements give some promising clues about the postmortem interval. A living human has a natural electrical conductivity; in the postmortem interval, intracellular fluids gradually leak out of cells. These leaked fluids combine with extra-cellular fluids in tissues and since both fluids are electrolytic, intracellular fluids help increase conductivity. Thus, the level of electrical conductivity is expected to increase with increased time after death. In this study, electrical conductivity tests were applied for six hours. The electrical conductivity of the cases exponentially increased during the tested time period, indicating a positive relationship between electrical conductivity and the postmortem interval. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Time of death estimation; Forensic medicine; Postmortem interval; Electrical conductivity; Body mass index; RIGOR-MORTIS; PHOTOMETRIC MEASUREMENT; BODY-TEMPERATURE; COOLING RATES; LIVOR-MORTIS; BRAIN; SEQUENCE; MUSCLE; LIVER; POTASSIUM; Life Sciences & Biomedicine - Other Topics; Computer Science; Engineering; Mathematical & Computational Biology